Prevention and Eradication of Terrorism Funding Criminal Act in Indonesia - Surwandono Surwandono; Tri Astuti Susanthi Retnoningsih; Masyithoh Annisa Alkatiri (Department of Government Studies Universitas Muhammadiyah Makassar, 2018)
Prevention and eradication of terrorism funding criminal acts have been published by Indonesian Government as a ratified act of International Convention for the suppression of the financing of terrorism under the Act No. 9 The Year 2013. This act was enacted for strategies and serious attempts to fight against transnational crime of terrorism. Through content analysis method on The Act, this research was meant to understand the direction of security regulation of Indonesia by using three paradigms i.e. realism, liberalism, and constructivism. It was figured out that realism was used by Indonesian Government of which the government acts as the key and dominant actor in this Act. This realistic paradigm implies on many government policies which are perceived overwhelming and tend to repress on civil right of freedom.